2012
DOI: 10.1055/s-0032-1315042
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Quenching and Antimicrobial Activity of Goldenseal (Hydrastis canadensis) against Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: The popular herbal remedy goldenseal (Hydrastis canadensis L.) is traditionally used to treat skin infections. With this study, we show activity of H. canadensis extracts in vitro against methicillin-resistant Staphylococcus aureus (MRSA). An extract from H. canadensis leaves demonstrated more potent antimicrobial activity than the alkaloid berberine alone (MICs of 75 µg/mL and 150 µg/mL, respectively). LC-MS detected alkaloids and efflux-pump inhibitory flavonoids in the extract, and the latter may explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Despite clearly representing a wealth of bioactive molecules, natural products have received limited attention with respect to identifying specific inhibitors of S. aureus QS that are not bactericidal. To date, other natural products identified as agr inhibitors include (i) ␣-cyperone from the nut grass plant Cyperus rotundus (93), (ii) the fungal metabolite ambuic acid (94), and extracts from (iii) the goldenseal plant Hydrastis canadensis (95) and (iv) three Italian medicinal plants, Ballota nigra, Castanea sativa, and Sambucus ebulus (96).…”
Section: Discussionmentioning
confidence: 99%
“…Despite clearly representing a wealth of bioactive molecules, natural products have received limited attention with respect to identifying specific inhibitors of S. aureus QS that are not bactericidal. To date, other natural products identified as agr inhibitors include (i) ␣-cyperone from the nut grass plant Cyperus rotundus (93), (ii) the fungal metabolite ambuic acid (94), and extracts from (iii) the goldenseal plant Hydrastis canadensis (95) and (iv) three Italian medicinal plants, Ballota nigra, Castanea sativa, and Sambucus ebulus (96).…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation found that extracts of goldenseal were able to inhibit the Agr signaling pathway of S. aureus, as determined by luciferase reporters that indicate quorum-sensing activity, and were shown to reduce alpha-toxin production (280). Application of the extracts to cultures of methicillin-resistant S. aureus (MRSA) grown with keratinocytes reduced keratinocyte toxicity incurred by the bacteria.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Application of the extracts to cultures of methicillin-resistant S. aureus (MRSA) grown with keratinocytes reduced keratinocyte toxicity incurred by the bacteria. Interestingly, the extracts were active against three of the four agr groups, indicating the active component has a generalized mechanism of inhibition against the signaling pathway (280). In addition to the benefits that a broad Agr inhibitor would provide as a therapeutic, the compound(s), once identified, will serve as a valuable molecular probe to help understand signal transduction of the Agr pathway.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Arrows represent the region of the chromatogram in which a given ion corresponding to a known constituent of H. canadensis (indicated by compound numbers) could be detected. Compounds 1 – 7 , 10 , 13 , 16 , 17 , 20 – 24 , and 28 were identified by comparison of retention time and fragmentation with authenticated standards, 20 while compounds 8 , 9 , 11 , 12 , 14 , 15 , 18 , 19 , and 25 – 27 were tentatively identified by comparison of accurate mass and molecular formula with literature reports. 22,24,27,29,33,36,37 29 is a new flavonoid that was isolated and identified based on NMR and MS data as part of this report.…”
Section: Figurementioning
confidence: 99%
“…18,19 Activity against the common Gram-positive bacterium Staphylococcus aureus was evaluated, given that H. canadensis has previously been shown to possess activity against this pathogen. 20 …”
mentioning
confidence: 99%